Permeability Of Interlanguage System: A Case Study Of Interlanguage System Of Junior High School Students Of SMP N 2 Surakarta Learning English As A Foreign Language - Syahrullah, Asep Shofian; , Prof. Dr. Endang Fauziati, M.Hum; , Phil. Dr. Dewi Chandraningrum, M.A (2015)
The present study aims at describing the permeability of interlanguage: a case study of interlanguage system of junior high school students of SMP N 2 Surakarta learning English as a foreign language. The objective of the study is to find out (1) the types of the students' native language (Indonesian) and the target language (English) influence into the students' interlanguage system; (2) the degree of the influence of Indonesian (as the students' native language) as well as the target language (English) into the students' interlanguage system. The type of the research is descriptive qualitative research. The writer uses elicitation technique and documentation in collecting data. The data of the present study consist of erroneous sentences taken from composition written by the students. In collecting the data, there are at least three major stages have been done: the writer assigned the students to write English composition, the writer reads every composition accurately to identify the erroneous sentences, the writers wrote down all the erroneous sentences into a list and used them as the data. In analyzing the data there are at least four major stages have been done, namely: identification of errors, classification, description, and explanation. To recognize the errors, the writer has utilized the framework provided by Shridar. The writer has accumulated approximately 288 sentences containing different type of errors and used as the data of this study. The errors accumulated, then, classified using comparative taxonomy in order to find out the influence of the students' native language (Indonesian) and the target language (English) into the students' interlanguage system The writer reaches the conclusion from this study as follows: (1) the students' interlanguage system is influenced by booth native language (Indonesian) and target language (English); (2) the influence is in the level of morphology and syntax; (3) the students' native language (Indonesian) contribute more influence compared with the target language (English) as the percentage shows 56.25% of Indonesian influence and 43.75% of English influence. Keywords: interlanguage system, permeability of interlanguage system, native language influence, target language influence.